Determining the perceptions and practices of oncologists regarding venous thromboembolism risk assessment in ambulatory cancer patients: A qualitative study - Marwa Akram Tariq; Ehab Mudher Mikhael (PLoS ONE, 2025)
Cancer-associated thrombosis (CAT) can increase morbidity and mortality for cancer patients. Therefore, guidelines recommend predicting VTE risk and thromboprophylaxis for high-risk patients. Many studies critique oncologists’ adherence to thromboprophylaxis guidelines for cancer patients. Meanwhile, most of these studies did not discuss in detail the reasons and facilitators for oncologists’ adherence to thromboprophylaxis guidelines. Therefore, the current study aimed to explore in depth the perceptions and practices of oncologists working in oncology centers in Baghdad, Iraq, regarding VTE and its risk assessment among ambulatory cancer patients. A qualitative study with face-to-face individual-based interviews was conducted with oncologists working in four major oncology centers in Baghdad, Iraq using a semi-structured interview guide. The guide was developed based on previous relevant literature and validated by a panel of experts. The interviews were conducted from November 2023 to January 2024. Thematic analysis approach was used for data analysis. Thirty-one oncologists were interviewed in this study. Twenty-two of the interviewed oncologists reported that they detect VTE among their cancer patients. 64% of participating oncologists reported that they did not conduct VTE risk assessments for their cancer patients. Only four oncologists reported assessing VTE risk using the Khorana score. 58% of oncologists reported that they prescribe thromboprophylaxis for high-risk patients; meanwhile, only 11% of them reported prescribing anticoagulants in a dose similar to that reported by thromboprophylaxis guidelines. 77% of participating oncologists reported that pharmacists have a significant role in preventing cancer-related thrombosis by helping physicians prescribe a safe and effective prophylactic anticoagulant and in calculating VTE risk scores. In conclusion, CAT is commonly diagnosed among Iraqi cancer patients. VTE risk assessment for ambulatory cancer patients is rarely conducted by oncologists working at Oncology centers in Baghdad, Iraq. The prophylactic anticoagulants were rarely prescribed in appropriate dose and/or duration for patients at high risk of VTE. Pharmacists can help oncologists follow thromboprophylaxis guidelines by calculating VTE risk score and recommending a safe and effective dose of appropriate prophylactic anticoagulant.Educating and training oncologists about VTE risk assessment is recommended to enhance their practice in thromboprophlaxis.